Snakes of India: The Field Guide - Romulus Whitaker and Ashok Captain (Westland Books Pvt Ltd, 2004)
This is the definitive color field guide to Indian snakes aimed at both amateurs and specialists. It concisely describes more than 150 species of snakes - both venomous and non - venomous. Many of the species covered in the book are also found in Nepal, Pakistan, Bhutan, Bangladesh and Sri Lanka. Snake identification is made easy through stunning photographs and includes many of the color variations found in Indian snakes. Each species account includes description, scalation, natural history, a distribution map and look alikes. Other sections include snakebite, snake people in India, laws protecting snakes and a complete up-to-date checklist.